Iberian epigraphy from Libisosa (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this work we analyze the Iberian inscriptions found in the excavations of Libisosa (Lezuza, Albacete), corresponding to the moment of destruction that has been related to the Sertorian Wars (82-72 BC). It is a corpus of 16 inscriptions written in southeast system. It is limited essentially to ceramic containers related to the storage and consumption of wine. The techniques used are the titulus pictus, the stamp and the graffito post-cocturam. In front of two tituli of hypothetical religious or ritual functionality, or the graffiti, perhaps property marks, the amphorae stamps, more numerous, are interpreted as production marks, highlighting the repetition of the same personal name -anbin(e)- in 7 pieces.
Keywords: Libisosa; Iberian epigraphy; South-Eastern writing system; Pottery